Evaluation of Potential Ergonomic Hazards Using the SNI 9011:2021 Method for Labeling Unit Workers in One of the East Java Agro-Industrial Company - Safitri, Rizka Wahyu; Rhomadhoni, Muslikha Nourma; Sahri, Moch.; Ayu, Friska (Universitas Nahdlatul Ulama Surabaya, 2023)
The industry's lack of attention to the implementation of ergonomics can give rise to complaints of Occupational Skeletal Muscle Disorders (GOTRAK) in workers. This research aims to evaluate the potential ergonomic hazards of labeling unit workers in one of the East Java Agro-industrial companies. This research is quantitative with a descriptive approach. The population of this study were labeling unit workers in one of the East Java Agro-industrial companies using a sampling technique, namely saturated sampling, totaling 21 respondents. The data collection technique was carried out using the SNI 9011:2021 method. The results of the GOTRAK complaint risk level study show that there are 6 parts of the skeletal muscles that have a high risk, namely the upper back muscles (47.6%), lower back (42.9%), left and right hands (28.6%), left hip and right (33.3%) and left knee (28.6%), and right knee (23.8%). The research results on potential ergonomic hazards stated that all respondents (100%) had a total potential ergonomic hazard score ≥ 7, including the dangerous category.